PENGEMBANGAN MODUL ELEKTRONIK BERBASIS GUIDED INQUIRY BERBANTUAN LABORATORIUM VIRTUAL PADA MATERI TERMODINAMIKA KELAS XI SMA - Hermawati, Farah Muthi; Purwanti, Popi; Noor, Iman; US, Supardi (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2024)
Abstract: 21st-century learning is closely related to the era of technological development of the Industrial Revolution 4.0. Learning using technology will help teachers explain learning material and also help students understand learning material. One of the technological developments in the world of education is the use of digital-based learning media. There are many types of digital-based learning media, one of which is electronic modules. This research aims to develop learning media in the form of electronic modules that are integrated with the syntax of the guided inquiry learning model and assisted by a virtual laboratory in its application. The development electronic module discusses thermodynamics material for class XI high school students. This research uses the ADDIE research method (Analyze, Design, Development, Implementation, and Evaluation) which is limited to the Development stage. The development of electronic modules has been validated by media experts and material experts. The assessment carried out by media experts obtained scores of 82.67% and 88.00% with the title